Development of contextual and AI-based e-learning media to increase poetry writing creativity - Konis Zaitun; Moh. Mu’minin; Sri Yanuarsih (Inovasi Kurikulum, 2025)
This study aims to develop contextual-based and artificial intelligence (AI)-based e-learning media to enhance the poetry writing creativity of Grade X vocational school students. The background of this study stems from the low ability of students in writing poetry, particularly in terms of diction, imagination, and the use of figurative language. The research employed a 4D development model (define, design, develop, disseminate). The media was developed in the form of an interactive module using Articulate Storyline, equipped with AI features that provide automatic feedback. Validation was conducted by six experts in content, language, and media. Practicality was tested using questionnaires administered to both teachers and students, while effectiveness was assessed through pretest and posttest results. Validation results indicated a high level of validity, with scores exceeding 96 percent. Practicality tests showed results of 92 percent from teachers and 93.36 percent from students. Effectiveness analysis revealed a classical completeness score of 92.86 percent. Based on these findings, the developed e-learning media is categorized as highly valid, practical, and effective for use in poetry writing instruction for Grade X vocational students.   Abstrak Penelitian ini bertujuan untuk mengembangkan media e-learning berbasis kontekstual dan berbasis artificial intelligence (AI) guna meningkatkan kreativitas menulis puisi peserta didik kelas X SMK. Latar belakang penelitian ini adalah rendahnya kemampuan menulis puisi peserta didik, terutama dalam hal diksi, imajinasi, dan pemanfaatan gaya bahasa. Penelitian ini menggunakan model pengembangan 4D (define, design, develop, disseminate). Produk media dikembangkan dalam bentuk modul interaktif berbasis Articulate Storyline dan dilengkapi fitur AI untuk memberikan umpan balik otomatis. Validasi dilakukan oleh enam validator yang terdiri atas ahli materi, bahasa, dan media. Uji kepraktisan dilakukan melalui angket kepada pendidik dan peserta didik, sedangkan uji keefektifan dilakukan melalui pretest dan posttest. Hasil validasi menunjukkan bahwa media tergolong sangat valid dengan tingkat kevalidan di atas 96persen. Hasil uji kepraktisan menunjukkan persentase sebesar 92 persen dari pendidik dan 93,36 persen dari peserta didik. Hasil uji keefektifan menunjukkan ketuntasan klasikal sebesar 92,86 persen. Berdasarkan hasil tersebut, media e-learning yang dikembangkan tergolong sangat layak, sangat praktis, dan sangat efektif digunakan dalam pembelajaran menulis puisi di kelas X SMK. Kata Kunci: AI; e-learning; media pembelajaran; menulis puisi; pembelajaran kontekstual